Extension theorems on L-topological spaces and L-fuzzy vector spaces - Pinchuck, Andrew (Rhodes University, Faculty of Science, Department of Mathematics, 2002)
A non-trivial example of an L-topological space, the fuzzy real line is examined. Various L-topological properties and their relationships are developed. Extension theorems on the L-fuzzy real line as well as extension theorems on more general L-topological spaces follow. Finally, a theory of L-fuzzy vector spaces leads up to a fuzzy version of the Hahn-Banach theorem.
Keywords: Topology; Vector spaces; Generalized spaces